Effecting the culture: Impact of changing urinalysis with reflex to culture criteria on culture rates and outcomes. (4th February 2023) - Penney, Jessica A.; Rodday, Angie Mae; Sebastiani, Paola; Snydman, David R.; Doron, Shira
Abstract: Objective: To evaluate the impact of changes to urinalysis with reflex to culture (UARC) reflex criteria on culture performance and clinical decision outcomes. Design: Retrospective study utilizing interrupted time series analysis from December 2018 to November 2020. Primary outcomes were measures of culture performance. Secondary outcomes were rates of antimicrobial prescription for suspected urinary tract infection (UTI) and catheter-associated urinary tract infection (CAUTI). We also assessed harmful events related to antimicrobial prescription for all causes and UTI, UTI symptoms, and sepsis. Setting: A 415-bed, academic, tertiary-care, medical center. Patients: Hospitalized adult patients with urine testing performed. Intervention: UARC reflex criteria were changed on October 22, 2019, from ≥5×10 9 /L white blood cells (WBCs) or trace leukocyte esterase or positive nitrite units on urinalysis to only ≥15×10 9 /L WBCs. Results: The study included 11, 322 unique UARC tests. We detected a significant decrease in the rate of urine cultures performed from UARC after the intervention (32.5–8.7 cultures per 1, 000 patient days; P < .001), with improved diagnostic efficacy (ie, culture positivity increased from 34.8% to 62.1%). CAUTI rates did not change. We detected a significant decrease in antimicrobial prescription rates ( P = .05), this was primarily driven by preintervention changes. One case of sepsis occurred secondary to a missed UTI, and UTIs were rarely missed after the intervention. Conclusions: Implementation of a stricter UARC reflex criterion was associated with a decrease in culture rates with improved diagnostic efficacy without significant adverse events. Continued education is needed to change antimicrobial prescribing practices.